The ant fauna of hospitals: advancements in public health and research priorities in Brazil - Castro, Mariana Monteiro de; Santos Prezoto, Helba Helena; Fernandes, Elisa Furtado; Bueno, Odair Correa [UNESP]; Prezoto, Fabio (Soc Brasileira Entomologia, 2015)
Ants inhabit several types of natural and urban habitats, where they successfully nest. In urban environments, the hospitals should be considered priority for studies, as ants pose risks to human health due to their pathogen carrying potential. We aimed at surveying the literature about studies on ants in hospital settings in Brazil in the past 20 years. We found 40 papers in 22 journals, the first one published in 1993. Among them, 26 papers assessed pathogenic microorganisms on ants. We recorded 59 ant species, being Tapinoma melanocephalum the most common. The Minas Gerais and Sao Paulo states had the largest number of published papers. Mato Grosso do Sul and Rio Grande do Sul showed the highest number of species. Exotic ant species were recorded in all states, except Goias. Considering the potential to carry microorganisms and the importance of thorough studies on the ecology of ant species, our results can support and guide further research in Brazil. (C) 2015 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Cross infection; Disease transmission; Microorganisms; Pest control